Metaphor: an Element of Imagery in Gerald Durrell’s “My Family and Other Animals” - Matevosyan, Armine; Nikoghosyan, Narine (Armenian Folia Anglistika, 2009)
The article examines metaphor which is one of the key expressive means in belles-lettres and has its unique place in the creation of imagery. The system of images in Gerald Durrel’s works is quite broad and various, made up of micro/macro images where the “aesthetic, cognitive and metaphoric potential of each leads to the creation of another image”. The article aims not only to analyze the metaphoric structures in Gerald Durrell’s works but also to view them as a means of creating imagery.